Prior Studies on Indonesian Populism: Historical Context, Core Elements, and Blind Spots - Hidayat, Rahmad (Jurnal Pemerintahan dan Politik Lokal, 2025)
Populism in Indonesia has been a crucial political phenomenon in recent decades, rooted in the nation's socio-political history. This article examines the historical context, core elements, and blind spots in prior research on Indonesian populism by analyzing 107 scholarly works published between 2001 and 2024 in the Scopus database. The findings reveal that Indonesian populism has evolved through various phases, from anti-colonial nationalist movements to contemporary digital populism, where social media plays a central role in mobilizing mass support and amplifying identity-based political narratives. The author identifies seven core elements shaping Indonesian populism, including its domains, antecedents, mobilization channels, and political consequences. The author also highlights blind spots in previous studies, specifically the limited focus on local-level populism, the long-term economic implications of populist policies, and the deepening societal polarization caused by digital populist discourse. By incorporating comparative perspectives with other Southeast Asian nations, this review broadens the understanding of populism’s regional dynamics. The findings contribute to academic discourse on populism and provide insights for policymakers in addressing the challenges posed by populist rhetoric and governance. Future research should explore empirical case studies on local populist movements and assess the impact of populist policies on democratic institutions in Indonesia.